2013
DOI: 10.1073/pnas.1305438111
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of plasma membrane H + -ATPase in guard cells promotes light-induced stomatal opening and enhances plant growth

Abstract: Stomatal pores surrounded by a pair of guard cells in the plant epidermis control gas exchange between plants and the atmosphere in response to light, CO 2 , and the plant hormone abscisic acid. Light-induced stomatal opening is mediated by at least three key components: the blue light receptor phototropin (phot1 and phot2), plasma membrane H + -ATPase, and plasma membrane inward-rectifying K + channels. Very few attempts have been made to enhance stomatal opening with the goal of increasing photosynthesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
182
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(195 citation statements)
references
References 41 publications
(54 reference statements)
10
182
0
Order By: Relevance
“…To the extent of our current knowledge, the results confirm past observations from a number of mutants, including the K + channel gork (Hosy et al, 2003), the anion channel slac1 (Negi et al, 2008;Wang et al, 2012), the ost2 H + -ATPase mutant (Merlot et al, 2007), the clca H + -Cl 2 antiporter mutant (De Angeli et al, 2006), and the tpk1 K + channel mutant (Gobert et al, 2007). They are supported, additionally, by the work of Wang et al (2014b), who concurrent with this publication reported the effects of overexpressing the several K + channels and the AHA2 H + -ATPase in Arabidopsis guard cells. Their results confirm the lack of effect on channel overexpression; they also demonstrate enhanced apertures, g s , and A with H + -ATPase overexpression.…”
Section: Ion Transport Stomatal Response and Wuesupporting
confidence: 87%
“…To the extent of our current knowledge, the results confirm past observations from a number of mutants, including the K + channel gork (Hosy et al, 2003), the anion channel slac1 (Negi et al, 2008;Wang et al, 2012), the ost2 H + -ATPase mutant (Merlot et al, 2007), the clca H + -Cl 2 antiporter mutant (De Angeli et al, 2006), and the tpk1 K + channel mutant (Gobert et al, 2007). They are supported, additionally, by the work of Wang et al (2014b), who concurrent with this publication reported the effects of overexpressing the several K + channels and the AHA2 H + -ATPase in Arabidopsis guard cells. Their results confirm the lack of effect on channel overexpression; they also demonstrate enhanced apertures, g s , and A with H + -ATPase overexpression.…”
Section: Ion Transport Stomatal Response and Wuesupporting
confidence: 87%
“…Using step changes in light intensity simplified the analysis. Incorporating the spectral definitions brings the OnGuard platform into alignment with current knowledge of the actions of light, especially of blue light, on the H + -ATPases (Takemiya et al, 2013;Wang et al, 2014b;Yamauchi et al, 2016) and will allow future refinements in model design, but it had no material effect on model output in our formulation.…”
Section: Methodsmentioning
confidence: 99%
“…Productive genotypes which also sustain growth and yield under variable moisture and temperature conditions express higher stomatal conductance and gas exchange (Shimshi and Ephrat 1975;Fischer et al 1998;Horie et al 2006;Blum 2011;Reynolds et al 2012;Blum 2013;Wang et al 2014). A study of triticale and durum wheat materials grown over different field environments (Motzo et al 2013) indicated that triticale had a consistently greater stomatal conductance than durum wheat during the vegetative stage and that this was associated with a respectively greater RUE.…”
Section: Potential Yieldmentioning
confidence: 99%